WHETHER TO PROCEED WITH A CIVIL PROCESS REMOTELY: UNIVERSAL LESSONS FROM AUSTRALIA DURING THE COVID-19 PANDEMIC - Nicci Whitear-Nel (Obiter, 2023)
This article considers Australian case law regarding testimony given by way of video link and the conducting of remote civil processes in the time prior to the COVID-19 pandemic, as well as during the pandemic and thereafter. The article discusses the various considerations taken into account by the courts in deciding whether or not to proceed remotely with civil processes. The author examines issues regarding whether to use video-conferencing, including the importance of the evidence and the architecture of the physical courtroom. The various issues facing lawyers in running a case remotely, including document management and the physical separation of legal teams, are also considered. The author looks also at issues facing the parties such as trial length, cost and the right of parties to be present, as well as issues facing other role players in the process, and issues pertaining to the integrity of the process. Lastly, issues relating to the administration of justice, such as access to justice and the open justice principle, are dealt with. The author concludes by commenting on the way forward and the lessons that can be extracted for South Africa.